TRANSFORMASI PEMBELAJARAN AL-QUR’AN MELALUI METODE TILAWATI: DAMPAK TERHADAP KELANCARAN DAN KUALITAS BACAAN SANTRI - Yuniarti, Nita; Juhro (An-Nahdlah: Jurnal Pendidikan Islam, 2025)
This study aims to describe the implementation of the Tilawati method in Qur’anic learning at Ma’had Muda’iyatul Anwar and to examine its pedagogical effectiveness and learning outcomes. Using a descriptive qualitative approach with a case study design, data were collected through classroom observation of 129 students, in-depth interviews with 41 respondents, and document analysis, then analyzed using the Miles and Huberman model. The Tilawati method, developed by KH. Masrur Masyhud and colleagues and consisting of six instructional volumes, is implemented through a structured combination of classical and individual learning using the baca-simak technique with the rost rhythm. Routine evaluations demonstrated significant progress: the proportion of students completing Juz 30 increased from 45% to 80%, and the average completion time was reduced from more than two years to approximately one year. The success was supported by teacher competence, adequate learning media, and institutional commitment, while challenges arose from unequal literacy levels, limited practice time, and high student–teacher ratios